Microfinance and its Impact on Indonesian Small to Medium Size Enterprise Productivity for Development - Yosua Christanto; Ahmad Danu Prasetyo (Sebelas Maret Business Review, 2019)
Microfinance is one of the key aspects that help the development of MSME, and it also applies globally. In many previous studies, there are no coherence about the impact of microfinance towards the development of MSME. We investigate the impact of microfinance to the development of MSME in Indonesia. Panel regression is the method that is utilized in this present study because the current data is in panel form which came from 32 provinces in Indonesia with the range of 2012-2014. Results indicated that there are two variables which are the number of microloans, HDI that significantly influence the development of MSME, microloans and HDI are negatively affected. The conclusion reflected the public views of Indonesian regarding entrepreneurship & MSME development. Entrepreneurship is viewed poorly by the public, society values working in cooperations are more valuable.The results of the research also indicated boundaries such as regulations, and views that obstructed the development of MSME in Indonesia.